2017
DOI: 10.1002/ccd.26979
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world supported unprotected left main percutaneous coronary intervention with impella device; data from the USpella registry

Abstract: This large singe center retrospective evaluation of USpella registry substantiates and strongly supports the feasibility, safety, and hemodynamic usefulness of Impella device for ULMI with acceptable in-hospital and 30-day MACE rates. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…However, all-cause death rates, for which the study was not powered, were similar between the two groups. Moreover, data regarding Impella supported PCI in patients undergoing unprotected left main (LM) revascularization have been extrapolated from the USpella registry [27] demonstrating its feasibility and safety. Although the analysis was mainly based on patients undergoing LM PCI, they achieved nearly complete revascularization with low procedural risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, all-cause death rates, for which the study was not powered, were similar between the two groups. Moreover, data regarding Impella supported PCI in patients undergoing unprotected left main (LM) revascularization have been extrapolated from the USpella registry [27] demonstrating its feasibility and safety. Although the analysis was mainly based on patients undergoing LM PCI, they achieved nearly complete revascularization with low procedural risk.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Schreiber et al [15] reported recently a single-center experience which demonstrated favorable in-hospital and 30-day survival (98.43% and 97.74%, respectively) among patients with depressed LV function (28.74±15.55%) and multiple comorbidities (Society of Thoracic Surgeon (STS) morbidity score of 23.6±12.04) who underwent prophylactic Impella support for a ULMCA PCI. The predicted surgical mortality estimated by the STS score in these patients was lower than the STS mortality score of our patients (3.59±3.63 vs. 6.06±6.57), suggesting a less sick patient population who might have been eligible for surgical revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a recently reported study suggest that in non-CS patients undergoing LMCA PCI, prophylactic insertion of the Impella ventricular assist device may be associated with improved procedural success rates and reduced complication rates [ 5 ]. Accordingly, Impella insertion prior to LMCA stenting may also be considered in selected hemodynamically stable patients with iatrogenic LMCA dissection.…”
Section: Discussionmentioning
confidence: 99%
“…The Impella device is a percutaneously inserted miniaturized ventricular assist device that is being increasingly used in the treatment of patients with acute myocardial infarction complicated by cardiogenic shock (AMICS) [ 1 4 ]. It has also been found to have a potentially valuable role in increasing the safety and efficacy of high-risk coronary interventional procedures (PCI), such as stenting of unprotected left main stem coronary artery (ULMCA) [ 5 ]. Using a retrograde femoral (or, occasionally, axillary) artery access, it is generally placed using standard percutaneous techniques in the left ventricular chamber (LV) across the aortic valve.…”
Section: Introductionmentioning
confidence: 99%